2023
DOI: 10.1186/s12885-023-11134-4
|View full text |Cite
|
Sign up to set email alerts
|

HER2-low breast cancer: evolution of HER2 expression from primary tumor to distant metastases

Abstract: Background Breast cancer (BC) with low human epidermal growth factor receptor 2 (HER2) expression is attracting much attention due to the breakthrough progress of novel anti-HER2 antibody-drug conjugates. HER2 expression is examined in patients with HER2-low BC and their distant metastases in this study, so as to further clarify the dynamic characteristics of HER2 low status in the process of disease progression. Methods Patients diagnosed with HER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Previous studies showed that molecular characteristics can vary between the primary tumor (PT) and distant metastases [ 12 , 13 , 14 ]. More specifically, discrepancies in HER2 expression between the PT and metastases could be shown in almost 50% of cases [ 15 , 16 ]. In addition to tumor plasticity [ 17 ], another explanation for these differences may be that early spreading cells differ from the PT or that specific subclones from the PT have a higher tendency to metastasize [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that molecular characteristics can vary between the primary tumor (PT) and distant metastases [ 12 , 13 , 14 ]. More specifically, discrepancies in HER2 expression between the PT and metastases could be shown in almost 50% of cases [ 15 , 16 ]. In addition to tumor plasticity [ 17 ], another explanation for these differences may be that early spreading cells differ from the PT or that specific subclones from the PT have a higher tendency to metastasize [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%